Naturally occurring mutations in the reverse transcriptase region of hepatitis B virus polymerase from treatment-naïve Korean patients infected with genotype C2 - Kim, Ji-Eun (World J Gastroenterol, 2017)
AIM: To report naturally occurring mutations in the reverse transcriptase region (RT) of hepatitis B virus (HBV) polymerase from treatment naïve Korean chronic patients infected with genotype C2. METHODS: Here, full-length HBV reverse transcriptase RT sequences were amplified and sequenced from 131 treatment naïve Korean patients chronically infected with hepatitis B genotype C2. The patients had two distinct clinical statuses: 59 patients with chronic hepatitis (CH) and 72 patients with hepatocellular carcinoma (HCC). The deduced amino acids (AAs) at 42 previously reported potential nucleos(t)ide analog resistance (NAr) mutation positions in the RT region were analyzed. RESULTS: Potential NAr mutations involving 24 positions were found in 79 of the 131 patients (60.3%). Notably, AA substitutions at 2 positions (rt184 and rt204) involved in primary drug resistance and at 2 positions (rt80 and rt180) that functioned as secondary/compensatory mutations were detected in 10 patients (1 CH patient and 9 HCC patients) and 7 patients (1 CH and 6 HCC patients), respectively. The overall mutation frequencies in the HCC patients (3.17%, 96/3024 mutations) were significantly higher than the frequencies in the CH patients (2.09%, 52/2478 mutations) (P = 0.003). In addition, a total of 3 NAr positions, rt80, rt139 and rt204 were found to be significantly related to HCC from treatment naïve Korean patients. CONCLUSION: Our data showed that naturally occurring NAr mutations in South Korea might contribute to liver disease progression (particularly HCC generation) in chronic patients with genotype C2 infections.